Use of pediatric logistic organ dysfunction in determining prognostic among pediatric intensive care unIt patIents - Lulu Honna; Silvia Triratna; Triwani Triwani; Theodorus Theodorus (Indonesian Pediatric Society, 2010)
Background Pediatric intensive care unit is the place for caring the children lith higher risk of mortality, usually with multiple organ dysfunction syndrome (MODS) that can increase difficulty in detennining prognostic. Th erefore, an objective severity of illness and organ dysfunction score is needed. Pediatric logistic organ dysfunction (PELOD) score can be considered as a representative for probability of death and predicting the prognostic.Objective To determine the prognostic of patients in PICU Mohammad Hoesin hospital (RSMH), Palembang, using PELOD score.Methods An observational study was conducted from April-September 2009 among PICU patients. PELOD score was assessed in the first 24 hour. S tatistical analysis was performed using Z-Mann Whitney test, Hosmer-Lemeshow goodness-of-fit, ROC curve and survival analysis Kaplan Meier (KM).Results There were 45 (55%) boys and 36 (44%) girls with mean age 51 (SD 6 ,4 7) months. Children with MODS were 75%. Death was 37 (45%) and survival was 44 (54%) with mean length of stay was 181,92 (SE 30,23) hours. PELOD score was from 0 to 51. The best PELOD score related to death in coordinate point was 20,5 with ROC 0,862. Length of stay in grup lith PELOD score < 20.5 was 371.22 (SE 82.13) hours and > 20.5 was 93 (SE 17.48) hours (log rank P=0.000). S urvival function KM showed that the higher PELOD score, the shorter length of stay in PICU.Henceforth, the higher probability prediction of mortality.Conclusion PELOD score can be used as a prognostic predictor of mortality among PICU patients in Mohammad Hoesin Hospital (RSMH), Palemhang.